P4_3 An Extra Minute - Szczykulska, Magdalena; Watson, Jason John; Garratt-Smithson, Lilian; Muir, Alistair William (Physics Special Topics, 2013)
This paper presents a case study of a meteor impact which would result in the addition of one extra minute to the period of the Earth's spin. Initial conditions are set and the meteor mass needed to produce this effect is calculated to be 1.54x1019 kg. The effect of the collision on the period of the Earth's precession about the spin axis is also calculated and found to be 18 years shorter than the current 26000 year value.